Adoption Of Islamic Trade Financing Facilities Among Smes In North-west Nigeria: A Preliminary Investigation - Nurudeen Abdulkadir; Safeza Mohd Sapian; Norhazlina Ibrahim (Penerbit Universiti Sains Islam Malaysia, 2024)
Volume 19 No: 1 (page: 63-85)